AGE AND GEODYNAMIC SETTINGS OF MIASKITE-PEGMATITES, CARBONATITES, AND Nb-Zr MINERALIZATION OF THE ILMENO-VISHNEVOGORSKY ALKALINE COMPLEX, SOUTH URAL (U-Pb AND Rb-Sr ISOTOPE DATA) - I. L. Nedosekova; V. S. Chervyakovsky; M. V. Chervyakovskaya; V. A. Bulatov (Геодинамика и тектонофизика)
The Ilmeno-Vishnevogorsky miaskite-phenite-carbonatite complex (IVС), located in the Urals folded region, is a representative of "linear type" carbonatite complexes, with which Nb-Zr deposits are associated. The ore potential of linear carbonatite complexes, the time and duration of ore-forming processes, and the geodynamic setting remain the subject of discussion. In order to estimate the age and duration of ore formation processes in the IVC, the U-Pb dating of zircon (LA-ICP-MS) from miaskite-pegmatites, as well as Rb-Sr dating of ore-bearing (pyrochlore-bearing) varieties of miaskite-pegmatites and carbonatites (ID-TIMS) were carried out. The U-Pb dating of zircon from the IVC miaskite-pegmatites showed the Permian age (280±8 Ma, P1 – age of the main zircon generation). The Rb-Sr-mineral isochron of miaskite-pegmatite showed a close age of 274±5 Ma (P1), confirming the results of U-Pb-dating of miaskite-pegmatites. The Rb-Sr dating of pyrochlore carbonatite varieties (sovites II) showed an age of 250±3 Ma (T1). The results of Rb-Sr- and U-Pb dating indicate that the processes of pegmatite- and carbonatite formation and the associated Zr-Nb ore formation in IVC occurred at the late collisional and postcollisional stage of development of the Ural folded region. Based on the data obtained, the geodynamic model for the IVC formation was proposed.